EVALUASI MULTI-KRITERIA TERHADAP KEBIJAKAN KARBON: KOMBINASI PENDEKATAN KUANTITATIF DAN KUALITATIF - Husmaruddin, Husmaruddin (Nusantara Hasana Journal, 2025)
This study analyzes the impact of the Emission Trading Scheme (ETS) and carbon tax on the economy and society in Indonesia using quantitative and qualitative methods. The quantitative method uses a dynamic system model to analyze the effect of carbon policy on greenhouse gas (GHG) emissions and economic growth. Simulation results show that carbon policy is effective in reducing GHG emissions, although it has a negative impact on gross domestic product (GDP), especially at high carbon prices. Qualitative methods involve surveys and interviews to evaluate the social impact of this policy. The results of the analysis show that the environmental and forestry sectors are more supportive of ETS, while the financial, service, and NGO and community sectors prefer carbon tax. Although carbon policy is effective in reducing GHG emissions, its economic and social impacts need to be taken into account. Therefore, the formulation of carbon policy must consider the balance between the effectiveness of emission reduction and its impact on various sectors to ensure economic sustainability and social welfare in Indonesia.